Pengaruh Keputusan Investasi dan Keputusan Pendanaan yang Dimediasi Oleh Risiko Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Sektor Aneka Industri Periode 2008-2012) - Meitri Handayani; Yulia Efni; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine direct and indirect effect of investment decision and financing decisionon business risk and firm value. Furthermore inderect effect on examined with testing investment decision and financing decision on firm value mediated by business risk. Purposive sampling is use to get our samples from fifty-four firms population that include in miscellaneous industry. We get twenty-one firms that used as our samples to analysis the data we use path analysis. The result show that investment decision didn’t influential toward risk, but financing decision is influentian toward risk. Investment decision didn’t influential toward firm value but financing decision is influentian toward firm value. and risk didn’t influential toward firm value. this indicates that risk varable only mediates the financing decision on firm value.Keywords: Investment Decisions, Financing Decision, Enterprise Risk and Firm Value